TEEM / PONDERING - útskriftarverk - Júlía Hrafnsdóttir 1999- (2021)
TEEM / IÐA ‘Teem’ is a celebration of eight different women and the inner dynamics of their sisterhood. The teeming force within them propels them into different structures and landscapes. Their energy is reflected in forces of nature with its source of life, conflicts, perseverance, and cycles. They rise as mountains, harden as lava and break like ocean waves. They are the earth and the air, the water and the fire, the calm and the storm. Credits: Choreographer: Anna Kolfinna Kuran in close collaboration with the dancers Composer & Sound designer: Ida Schuften Juhl Costume & Set designer: Guðný Hrund Sigurðardóttir Costume designer & maker: Mao Alheimsdóttir Lighting Designer: Valdimar Jóhannsson Video Visuals: Katerina Blahutova Photographer: Antje Taiga Jandrig Song: Nocturne lyrics Eino Leino composer Perttu Hietanen & Taisto Wesslin // PONDERING / VIÐ TJÖRNINA In a world rank with anticipation and regret, somewhere between hope and revenge lies The Pond. Take a step back into the future as you witness events that are none of your damn business. Credits: Choreographers: Cameron Corbett & Ásgeir Helgi Magnússon Movement & text inspired by collaboration with the performers. Lighting Designer & Sound: Valdimar Jóhannsson Costumes: Ásgeir Helgi Magnússon & Cameron Corbett Music: Tchaikovsky, Cage, Saint-Saëns Photographer: Antje Taiga Jandrig Pondering is a part of the research project Svannavatnið which received funding from the Professional Performance Art Groups Fund